The utility of 1-minute sit-to-stand test to detect exercise-induced oxygen desaturation in outpatient assessment of post COVID-19 patients. - M. A., Ibrahim; M. N., Kamarudin; Chai, Chee Shee; M. F., Abdul Rani (European Respiratory Society, 2022)
Introduction: The 6-min walk test (6MWT) is the gold standard for assessing exercise-induced impairment of gas exchange, but it is technically challenging in a busy outpatient clinic. The aim of this study was to compare the 1-min sit-to-stand test (1STST) with the 6MWT in assessment of exercise-induced oxygen desaturation in post COVID-19 patients in an outpatient setting.